Will AI replace us? : a primer for the 21st century - Fan, Shelly (Big idea (Thames and Hudson), 2019)
The past sixty years have witnessed astonishing bursts of growth in the field of Artificial Intelligence - the science and computational technologies that teach machines to sense, learn, reason and take action. AI is already changing our lives, in ways that benefit health, productivity and entertainment. Are we on the threshold of an AI-dominated world, in which humans will no longer be necessary?